Christ under the rubble : Bonhoeffer on aesthetic existence in the church as a sphere of freedom in a time of war - De Gruchy, John (Stellenbosch Theological Journal, 2024)
In a brief comment from prison Dietrich Bonhoeffer asks how anyone can be happy in a time of war. In response he writes about founding aesthetic existence anew in the church. This essay examines what he meant by this in our own “time of war”. First, by considering Kierkegaard’s rejection of aestheticism, his affirmation of “living poetically” and the “passion of possibility.” Secondly, by recounting Bonhoeffer’s own journey from his early humanist formation and travels abroad to his involvement in the Resistance and imprisonment. Thirdly, by examining what Bonhoeffer meant by the church as a “sphere of freedom”. Fourthly, I discuss the examples Bonhoeffer suggests for nurturing aesthetic existence in the church (art, formation, friendship, and play). I wonder whether … it is only from the concept of the church that we can regain the understanding of the sphere of freedom (art, education, friendship, play). This means that aesthetic existence (Kierkegaard) is not to be banished from the church’s sphere; rather, it is precisely within the church that it would be founded anew. I actually believe this, and from here we could recover our connection with the Middle Ages! Who in our time could, for example, light-heartedly make music, nurture friendship, play, and be happy? Certainly not the “ethical” person, but only the Christian (Dietrich Bonhoeffer). The startling nativity scene of “Christ under the Rubble”, displayed in the Lutheran Church in Bethlehem during Advent 2023 was an icon of solidarity with the Palestinian people during the war on Gaza. Irrespective of how we evaluate it as a “work of art”, it is testimony to God’s incarnational solidarity with the suffering people of the world and an example of the prophetic role of art. How to understand that role within church and society and its theological significance led me to write Christianity, Art and Transformation twenty years ago. In doing so, I became more aware of the remarkable role that art in its various forms played in the struggle against apartheid, much of it outside the church. While it was important to recall and reflect on the role of art in the anti-apartheid struggle, my focus in writing Christianity, Art and Transformation was on the potential role of art in the creation of a more just world global society. In doing so I discussed Bonhoeffer’s passing comment on aesthetic existence, quoted above, in a letter from prison to Eberhard and Renate Bethge, his close friend and niece. That discussion was developed further by Adrian Coates in his dissertation published as The Aesthetics of Discipleship, and in a later essay on Bonhoeffer’s understanding of “mature aesthetics.” In what follows I take that discussion further with specific reference to ecclesiology within an unjust global context defined by war, most notably but not only in the Sudan, Ukraine and Palestine.